Smart Green Infrastructure in Tiger Range Countries : A Multi-Level Approach - Quintero, Juan D.; Roca, Roberto; Morgan, Alexis; Mathur, Aradhna; Shi, Xiaoxin (World Bank, Washington, DC, 2017)
This report presents the results of extensive work of the smart green infrastructure task force commissioned by the World Bank under the Global Tiger Initiative (GTI). The report benefited from advice, ideas, and information about tigers and tiger-friendly infrastructure development from staff at the World Bank, and from several institutions that promote tiger and biodiversity conservation throughout the world. This study addresses infrastructure's impacts on tigers at international, national, sectoral and project levels in combination with the mitigation hierarchy which is based on avoidance, mitigation, minimization and compensation of impacts. It examines infrastructure policy challenges and opportunities, using lessons learned from case studies, along with regional and in-country analyses. While there are opportunities for improvement in all countries, Russia, India, Bhutan, and Nepal has, in particular, developed good foundations for tiger-related conservation, planning, and policy efforts. Best practices, drawn from case studies in non-tiger range countries, provide additional insights into infrastructure practices that could benefit tiger populations. Avoiding Tiger Conservation Landscapes (TCLs) is the best and cheapest option available to all parties for saving wild tigers.